Production, Optimization of Detoxification and Ammonium Sulphate Precipitation of Ultrafiltered Tetanus Toxin - Tejpal Kashyap2, Chandani Payal1,2,3* and (Recent Research in Science and Technology, 2011)
The present project work was undertaken with the aim of producing a safe & potent tetanus toxin by static culture method, optimization of detoxification process for the conversion of toxin to toxoid and its purification by ammonium sulphate precipitation. Tetanus toxin can be converted into a safe, highly potent and irreversibly detoxified vaccine either using the conventional method in which the crude toxin is chemically detoxified and subsequently purified or by formalization of the purified toxin in the presence of artificial matrix. In this study, we evaluated another approach for preparation of tetanus toxoid by concentrating and partially purifying the toxin followed by detoxification with formaldehyde-stabilizing agent mixture.Ã‚Â The increase in purity was observed after ultrafiltration of crude tetanus toxin. So ultra-filtration is useful for the partial purification of tetanus toxin. The toxin was detoxified completely within 4 weeks of incubation both in the presence and absence of stabilizing agents. The pH and lf/ml value of the toxin decreased during 6 weeks of incubation at 37Ã‚Â°C of the toxoid. According to the preliminary curve, the tetanus toxoid was found to precipitate between 12 to 24% concentration of ammonium sulphate.